An Energy Efficient Routing Protocol Based On New Variable Data Packet (VDP) Algorithm for Wireless Sensor Networks - Chandrawanshi, Veervrat S.; Tripathi, Rajiv Kumar; Pachauri, Rahul; Khan, Nafis Uddin (Recent Advances in Computer Science and Communications, 2020)
Background: Wireless Sensor Networks (WSNs) refer to a group of sensors used for sensing and monitoring the physical data of the environment and organizing the collected data at a central location. These networks enjoy several benefits because of their lower cost, smaller size and smarter sensors. However, a limited source of energy and lifetime of the sensors have emerged as the major setbacks for these networks. Methods: In this work, an energy-aware algorithm has been proposed for the transmission of variable data packets from sensor nodes to the base station according to the balanced energy consumption by all the nodes of a WSN. Result: Obtained simulation results verify that the lifetime of the sensor network is significantly enhanced in comparison to other existing clustering based routing algorithm. Conclusion: The proposed algorithm is comparatively easy to implement and achieves a higher gain in the lifetime of a WSN while keeping the throughput nearly same as LEACH protocol.
Keywords: energy efficient routing